Smartphones and children’s mathematics - Przybyła, Tomasz; Basińska, Anna; Klichowski, Michał (Wydawnictwo Naukowe UAM, 2014)
This article aims to show how children act in the world full of media, while presenting some smartphone applications that can help children learn mathematics.
Keywords: smartphone; learning mathematics; children; educational technologies; educational media